Filtration of palm oil milling effluent (POME) using kenaf: article - Mohd Zikeri, Muhammad Zharith; Jaapar, Jefri; Musa, Mohibah (2017)
Palm Oil Mill Effluent (POME) is a waste water generated that contains huge amount of toxicity because of its high content of heavy metals, discharged from sterilization process, crude oil clarification and cracked mixture separation process. Due to its chemical content, POME is not suitable to be released to nature as it will inhibit natural life. On the other hand, Kenaf is a southern Asia-native plant that are now world-widely used as pulp and paper manufacturing. Some studies have stated the potential ability of kenaf to be used as a filter material, with cost effective factor is in play. This paper will demonstrate the ability of kenaf as filter, in pretreating POME.